The Use of English Song to Improve Listening Comprehension Achievement of Junior High School Students - Amelia, Mely Dewi Nur; Tasnim, Zakiyah; Fardhani, Aan Erlyana (English Education Study Program, 2024)
This research investigated improving the students' listening comprehension achievement by using English songs. The research design was Classroom Action Research (CAR). The research area was Madrasah Ibtidaiyah which is under the auspices of the Alyasini Integrated Islamic Boarding School Foundation located in Pasuruan and the subjects of this research were Grade VIII-E students chosen purposively by using purposive method. The data were collected from interview, listening comprehension test, observation, and documentation. The results of this research showed that the results of observation showing that out of 30 students in the class, 25 students (83.33%) participated actively in the teaching-learning process by using English songs. Then, in the listening comprehension test, there was an increase from 19 students, or 63.33%, who achieved the target score before the action of the cycle to 26 students, or 86.67%, who achieved the target score after the action of the cycle model. This means that using English song could improve the students' participation and their listening comprehension achievement.